تاثير صناع المحتوى في مواقع التواصل الاجتماعي على قيم وسلوك المراهق - عليه، شيماء (جامعة الوادي university of Eloued, 2021)
الملخص: سعت هذه الدراسة الى معرفة تأثير صناع المحتوى في مواقع التواصل الاجتماعي على قيم وسلوك المراهق، لتجيب على التساؤل الرئيسي وهو: ما مدى تأثير صناع المحتوى في مواقع التواصل الاجتماعي على قيم وسلوك المراهق؟ والتساؤلات الفرعية التي جاءت كالتالي: - كيف يتعرض المراهقين لمحتويات صناع المحتوى في مواقع التواصل الاجتماعي؟ - ماهي القيم المبثوثة من طرف صناع المحتوى في مواقع التواصل الاجتماعي؟ - هل أدى تكرار تعرض المراهقين لمحتويات صناع المحتوى في مواقع التواصل الاجتماعي الى ظهور سلوكيات جديدة؟ معتمدة في ذلك على المنهج الوصفي، وعلى الاستبيان والملاحظة كأدوات للدراسة، الذي وزع على عينة عمدية متمثلة في فئة المراهقين، قوامها 100 مفردة. حيث توصلت الدراسة الى جملة من النتائج أهمها: - ان الموقع المفضل بالنسبة للمبحوثين هو موقع انستغرام، حيث ان اغلبية المبحوثين يتابعون محتويات صناع المحتوى لأكثر من ساعتين. - يفضل المبحوثين مجال الكوميديا وأسلوب الحياة. - يرى المبحوثين ان صناع المحتوى يبثون قيما حسنة وأبرزها قيمة التكافل الاجتماعي، وهذا لا ينفي انهم يبثون قيما سلبية أيضا. - أثر صناع المحتوى في سلوكيات المراهقين، من ناحية الملبس، ونشرهم المستمر لصورهم في مواقع التواصل الاجتماعي. وبناءا على النتائج السابقة، وبعد التطرق لخصائص صناع المحتوى في الجانب النظري، يمكن تصنيفهم ضمن قادة الرأي الرقميين، وتسميتهم ب “المؤثرين". Résumé : This study aims to know the impact of content creators in social media on the values and behavior of adolescents, to answer the main question: What is the extent of the influence of content makers in social media on the values and behavior of adolescents? Sub-questions: - How are teenagers exposed to the content of content creators on social media? - What are the values disseminated by content creators on social media? - Did the frequent exposure of teenagers to the content of content creators in social media lead to the emergence of new behaviors? I relied on the descriptive approach, and on the questionnaire and the Remarque as a tool for the study, which was distributed to a deliberate sample of adolescents, consisting of 100 teenagers. The study reached a number of results, the most important of which are: - The favorite site for respondents is Instagram, as the majority of respondents have been following content creators for more than two hours. - The respondents preferred the domain of comedy and lifestyle. - The respondents believe that content makers transmit good values, most notably the value of social solidarity, and this does not negate that they transmit negative values as well. - The impact of content creators on the behavior of adolescents, in terms of clothing, and their continuous publication of their photos on social media. Based on the previous results, and after discussing the characteristics of content makers in theory, they can be classified among the digital opinion leaders, and called them “influencers”.
دراسة ميدانية على عينة من تلاميذ الثانويات
مذكرة ماستر إعلام تخصص سمعي بصري
Keywords: مواقع التواصل الإجتماعي، صناع المحتوى، المراهقة، الغرس الثقافي; Réseaux sociaux, créateurs de contenu, adolescence, implantation culturelle; Social media, content creators, adolescence, cultural implantation